Politicizing Digital Space Theory, the Internet, and Renewing Democracy - Garrisson Smith, Trevor (University of Westminster Press, 2017)
"The objective of this book is to outline how a radically democratic politics can be reinvigorated in theory and practice through the use of the internet. The author argues that politics in its proper sense can be distinguished from anti-politics by analyzing the configuration of public space, subjectivity, participation, and conflict. Each of these terrains can be configured in a more or less political manner, though the contemporary status quo heavily skews them towards anti-political configuration. Using this understanding of what exactly politics entails, this book considers how the internet can both help and hinder efforts to move each area in a more political direction. By explicitly interpreting contemporary theories of the political in terms of the internet, this analysis avoids the twin traps of both technological determinism and technological cynicism. Raising awareness of what the word 'politics' means, the author develops theoretical work by Arendt, Rancière, Žižek and Mouffe to present a clear and coherent view of how in theory, politics can be digitized and alternatively how the internet can be deployed in the service of trulydemocratic politics."